ESTABLISHING CONTENT VALIDITY OF THE FACE-Q CRANIOFACIAL MODULE FOR PEDIATRIC HEAD AND NECK CANCER - Wang, Yi (My University, 2020)
Objective: Existing patient-reported outcome measures (PROM)s for patients with facial differences lack content validity, as few items address appearance and function issues. The FACE-Q is a new PROM developed to measure outcomes important to patients aged 8-29 years with craniofacial conditions. A process was needed to determine if the FACE-Q content is relevant to patients with head and neck cancer (HNC). Methods: Cognitive interviews with patients with HNC aged 8 to 29 years (n=15) were conducted and feedback from experts in pediatric oncology (n=21) was obtained. Input was sought on all aspects of the FACE-Q content. Results: A total of 1573 codes were developed from patient comments and 234 codes were developed from expert feedback that related to the COSMIN criteria for judging content validity. A total of 12 items were flagged for review from qualitative interviews and 4 comments were coded from expert feedback among the core scales for comprehensibility. Instructions, time frame, and response options were found to be comprehensible and appropriate by almost all patient and expert participants. Participants identified a total of 10 missing items identified across the core scales, while no additional items were identified by experts for the core scales. However, 4 experts identified swallowing/dysphagia as an important item missing from the mouth function scale. Discussion: Content validity of the FACE-Q for patients with HNC was evaluated through cognitive interviews with patients and feedback from pediatric oncology experts. The core scales were answered by all participants and demonstrate overall content validity from feedback offered by both patients and experts. Conclusion: The FACE-Q showed evidence of content validity for its core scales along with limited evidence that the remaining scales covered issues relevant to specific HNC patients. Assessment of the psychometric properties of the new measure is forthcoming as part of an international FACE-Q field-test study.
CONTENT VALIDITY OF FACE-Q FOR PEDIATRIC HEAD AND NECK CANCER
Keywords: oncology; head and neck cancer; facial difference; FACE-Q; quality of life